QTL mapping of pre-harvest sprouting and stripe rust resistance in wheat cultivars Danby and Tiger - Shao, Mingqin (Kansas State University, 2017)
Wheat yield and quality is influenced by many abiotic and biotic environmental factors. Pre-harvest sprouting (PHS) occurs when physiologically matured spikes are exposed to wet field conditions before harvest, which results in seed germination and causes significant losses in yield and end-use quality. Wheat stripe rust is one of the most important biotic factors reducing grain yield and quality. To investigate the genetic basis of the resistance to PHS and stripe rust in hard white winter wheat cultivars Danby and Tiger and develop molecular markers for marker- assisted breeding, a double haploid (DH) population, derived from those two cultivars, was genotyped with simple sequence repeats (SSR) markers and simple nucleotide polymorphism (SNP) markers. This DH population was assessed for resistance to PHS and stripe rust in both greenhouse and field experiments. For PHS, one major resistant quantitative trait locus (QTL) was consistently detected on the short arm of chromosome 3A in all three experiments conducted and explained 21.6% to 41.0% of the phenotypic variation (PVE). This QTL is corresponding to a previously cloned gene, TaPHS1. A SNP in the promoter of TaPHS1 co- segregated with PHS resistance in this mapping population. Meanwhile, two other QTLs, Qphs.hwwg-3B.1 and Qphs.hwwg-5A.1, were consistently detected on the chromosome arms 3BS and 5AL in two experiments. These two QTLs showed significant additive effects with TaPHS1 in improving PHS resistance. For stripe rust, three major QTLs were consistently detected in four out of six environments for infection type (IT) or disease severity (DS). Two of them, QYr.hwwg-2AS1 and QYr.hwwg-4BL1, contributed by the Danby allele explained up to 28.4% of PVE for IT and 60.5% of PVE for DS. The third QTL, QYr.hwwg-3BS1, contributed by the Tiger allele, had PVE values up to 14.7% for IT and 22.9% for DS. QYr.hwwg-2AS1 and QYr.hwwg- 4BL1 are likely the same resistance genes reported previously on chromosome arms 2AS and 4BL. However, QYr.hwwg-3BS1 might be different from the reported gene cluster near the distal end of 3BS where Yr57, Yr4, Yr30 and Sr2 were located. Significant additive effects on reducing IT and DS were observed among these three major QTLs. In order to pyramid multiple QTLs in breeding, user-friendly Kompetitive allele specific PCR (KASP) markers were successfully developed for several QTLs identified in this study. The QTLs and their interactions found in this study together with those novel flanking KASP markers developed will be useful not only for understanding genetic mechanisms of PHS and stripe rust resistance but also for marker- assisted breeding to improve wheat resistance to PHS and stripe rust by gene pyramiding.
Keywords: Wheat; Pre-harvest sprouting; Stripe rust; Resistance QTL mapping; Genotyping by sequencing; Molecular markers